1983
DOI: 10.1620/tjem.139.355
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of interferon on influenza virus infection in mice.

Abstract: The antiviral effect of highly purified mouse interferon (IFN) was studied on influenza virus infection in mice, by changing the routes of administration. By repeated intravenous (iv.) administrations of IFN, no antiviral effect was observed. However, IFN was effective when the infected mice received either intraperitoneal (i.p.) or intranasal (in.) administrations. While all of the untreated mice died within 10 days after infection, 20% of the i.p. treated mice and 67% of the i.n. treated mice survived more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…We have previously demonstrated that local IFN, particularly in lungs, is very important to the survival of mice exposed to influenza virus (21,30,31). When 5 ϫ 10 5 U of IFN per kg was given to mice intravenously, no protective effect was obtained and only 4 ϫ 10 2 U of IFN per lung was detected in lung homogenates 15 min after administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that local IFN, particularly in lungs, is very important to the survival of mice exposed to influenza virus (21,30,31). When 5 ϫ 10 5 U of IFN per kg was given to mice intravenously, no protective effect was obtained and only 4 ϫ 10 2 U of IFN per lung was detected in lung homogenates 15 min after administration.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we described the protective effect of GR on influenza virus infection in mice and how the IFN response stimulated by GR is involved in the protection of mice exposed to the virus. Some reports have described the effect of exogenous IFN against influenza virus infection (21,30). Usually, in FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the route of administration, IFN has been shown to influence influenza virus infection in vivo (33). Indeed, since influenza viruses are capable inducers of IFN, it is plausible that apoptosis via FADD contributes to the acute respiratory disease that epitomizes this particular orthomyxvirus infection (11a).…”
Section: Discussionmentioning
confidence: 99%
“…Ряд сообщений описывают действие экзогенного IFN против гриппозной инфек-ции [29,32]. Кроме того, во многих сообщени-ях описано противовирусное действие индук-торов IFN, таких как 9-метилстрептимидон и декстранфосфат, на гриппозную инфекцию у мышей [28,31,32,33,35,36].…”
Section: иммуномодулирующая активностьunclassified